Experimental determination of the electrostatic nature of carbonyl hydrogen-bonding interactions using IR-NMR correlations - Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemical Letters, 2014)
Hydrogen-bonding plays a fundamental role in the structure, function, and dynamics of various chemical and biological systems. Understanding the physical nature of interactions and the role of electrostatics in hydrogen-bonding has been the focus of several theoretical and computational research. We present an experimental approach involving IR-C-13 NMR correlations to determine the electrostatic nature of carbonyl hydrogen-bonding interactions. This report provides a direct experimental evidence of the classical nature of hydrogen-bonding interaction in carbonyls, independent of any theoretical approximation. These results have important implications in chemistry and biology and can be applied to probe the reaction mechanisms involving carbonyl activation/stabilization by hydrogen bonds using spectroscopic techniques.

Cosolvent effects on solute-solvent hydrogen-bond dynamics: ultrafast 2D IR investigations - Kashid, Somnath M.; Jin, Geun Young; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry B, 2015)
Cosolvents strongly influence the solute-solvent interactions of biomolecules in aqueous environments and have profound effects on the stability and activity of several proteins and enzymes. Experimental studies have previously reported on the hydrogen-bond dynamics of water molecules in the presence of a cosolvent, but understanding the effects from a solute's perspective could provide greater insight into protein stability. Because carbonyl groups are abundant in biomolecules, the current study used 2D IR spectroscopy and molecular dynamics simulations to compare the hydrogen-bond dynamics of the solute's carbonyl group in aqueous solution, with and without the presence of DMSO as a cosolvent. 2D IR spectroscopy was used to quantitatively estimate the time scales of the hydrogen-bond dynamics of the carbonyl group in neat water and 1:1 DMSO/water solution. The 2D IR results show spectral signatures of a chemical exchange process: The presence of the cosolvent was found to lower the hydrogen-bond exchange rate by a factor of 5. The measured exchange rates were 7.50 X 10(11) and 1.48 X 10(11) s(-1) in neat water and 1:1 DMSO/water, respectively. Molecular dynamics simulations predict a significantly shorter carbonyl hydrogen-bond lifetime in neat water than in 1:1 DMSO/water and provide molecular insights into the exchange mechanism. The binding of the cosolvent to the solute was found to be accompanied by the release of hydrogen-bonded water molecules to the bulk. The widely different hydrogen-bond lifetimes and exchange rates with and without DMSO indicate a significant change in the ultrafast hydrogen-bond dynamics in the presence of a cosolvent, which, in turn, might play an important role in the stability and activity of biomolecules.

Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.

Pick and choose the spectroscopic method to calibrate the local electric field inside proteins - Haldar, Tapas; Kashid, Somnath M.; Deb, Pranab; Kesh, Sandeep; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Electrostatic interactions in proteins play a crucial role in determining the structure function relation in biomolecules. In recent years, fluorescent probes have been extensively employed to interrogate the polarity in biological cavities through dielectric constants or semiempirical polarity scales. A choice of multiple spectroscopic methods, not limited by fluorophores, along with a molecular level description of electrostatics involving solute-solvent interactions, would allow more flexibility to pick and choose the experimental technique to determine the local electrostatics within protein interiors. In this work we report that ultraviolet/visible-absorption, infrared-absorption, or C-13 NMR can be used to calibrate the local electric field in both hydrogen bonded and non-hydrogen bonded protein environments. The local electric field at the binding site of a serum protein has been determined using the absorption wavelength as well as the carbonyl stretching frequency of its natural steroid substrate, testosterone. Excellent agreement is observed in the results obtained from two independent spectroscopic techniques.

Two-dimensional infrared spectroscopy reveals cosolvent-composition-dependent crossover in intermolecular hydrogen bond dynamics - Kashid, Somnath M.; Jin, Geun Young; Chakrabarty, Suman; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2017)
Cosolvents have versatile composition-dependent applications in chemistry and biology. The simultaneous presence of hydrophobic and hydrophilic groups in dimethyl sulfoxide (DMSO), an industrially important amphiphilic cosolvent, when combined with the unique properties of water, plays key roles in the diverse fields of pharmacology, cryoprotection, and cell biology. Moreover, molecules dissolved in aqueous DMSO exhibit an anomalous concentration-dependent nonmonotonic behavior in stability and activity near a critical DMSO mole fraction of 0.15. An experimental identification of the origin of this anomaly can lead to newer chemical and biological applications. We report a direct spectroscopic observation of the anomalous behavior using ultrafast twodimensional infrared spectroscopy experiments. Our results demonstrate the cosolventconcentration-dependent nonmonotonicity arises from nonidentical mechanisms in ultrafast hydrogen-bond-exchange dynamics of water above and below the critical cosolvent concentration. Comparison of experimental and theoretical results provides a molecular-level mechanistic understanding: a distinct difference in the stabilization of the solute through dynamic solute solvent interactions is the key to the anomalous behavior.

Arresting an unusual amide tautomer using divalent cations - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Ion-specific effects on peptides and proteins are key to biomolecular structure and stability. The subtle roles of the cations are far less understood, compared to the pronounced effects of the anions on proteins. Most importantly, divalent cations such as Ca2+ and Mg2+ are crucial to several biological functions. Herein, we demonstrate that an amide-iminolate equilibrium is triggered by the binding of the divalent cations to the amide oxygen in aqueous solution. The excellent agreement between the experimental and theoretical results confirms the arrest of an unusual amide tautomer by the divalent cations, which is a rarely known phenomenon that might open up an array of applications in chemistry and biology.

Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Reply to “comment on ‘arresting an unusual amide tautomer using divalent cations’” - Kashid, Somnath M.; Singh, Reman K.; Kwon, Hyejin; Seol, Jin Gyu; Kim, Yung Sam; Mukherjee, Arnab; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
In our publication, we assigned the blue-shifted shoulder of N-methylacetamide (NMA) in the infrared (IR) spectrum (∼1645 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1) to an iminolate tautomer stabilized in the presence of divalent metal cations (e.g., 5 M Ca<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2+).<a class="ref ref1" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(1) Cremer and co-workers comment that this shoulder arises from the dehydration of the amide oxygen upon interaction with the metal cations.<a class="ref ref1a ref2" style="outline: none; background-color: transparent; text-decoration-line: underline; color: rgb(26, 13, 171); transition: color 0.3s ease 0s; overflow-wrap: break-word; word-break: break-word; display: inline-block; font-family: Roboto, arial, sans-serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">(2,3) Their assignment is based on three interesting experimental observations: (1) the IR spectrum of <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-isotope-labeled NMA does not show any considerable red-shift compared to that of NMA; (2) a new peak appears for NMA at 1680 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 in the presence of 1 M DCl, which shows a 17 cm<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">–1 red-shift for <span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; top: -0.5em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">15N-labeled NMA; and (3) the IR spectrum of acetone C═O stretch also demonstrates a blue-shifted shoulder in the presence of a high concentration of CaCl<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Roboto, arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300;">2.